The effect of management of transport and lairage conditions on broiler chicken breast meat quality and DOA (Death on Arrival) - Oba,Alexandre (2009)
The aim of this work was to evaluate the influence of time of broiler chicken transportation and lairage prior to slaughtering on the occurrence of PSE (Pale, Soft, Exudative) meat and Death On Arrival (DOA) under non-commercial conditions in the Brazilian summer. Male birds (n=250) from a commercial line were subjected to different periods of journey (30, 90, and 180 min) and lairage (0, 90, and 180 min) before slaughtering. The occurrence of PSE was higher in broilers subjected to shorter journeys and lairage periods, whereas DOA was more pronounced upon longer periods of transport and lairage. The DOA occurrence percentage was much higher in comparison to commercially available figures, confirming that broiler chickens are very sensitive to both transport and lairage maneuvers.